The therapeutic potential of γ-Al2O3 nanoparticle containing 5-fluorouracil in the treatment of colorectal cancer. (June 2022) - Fasihi, Khadije; Amerizadeh, Forouzan; Sabbaghzadeh, Reihaneh; Heydari, Maryam; Rahmani, Farzad; Mostafapour, Asma; Khazaei, Majid; Rasouli, Elisa; Hassanian, Seyed Mahdi; Ferns, Gordon A.; Rezayi, Majid; Avan, Amir
Highlights: 5-Fluorouracil (5-FU) is being used in the treatment of several malignancies, but several side effects are commonly reported. Indicating here we have developed and tested the cytotocic activity of nanocrystalline powder of γ-alumina (γ-Al2 O3 ) containing 5-FU in two-dimensional and three-dimensional (3D) CRC cells. The effect of γ-Al2 O3 -5-FU on cancer cell oxidative stress induction was evaluated. γ-Al2 O3 -5-FU inhibited cell growth in two-dimensional (2D) and three-dimensional (3D) cell culture and increased apoptosis as detected by DAPI stainning via modulation of Caspases, BAx, BCl2 and cyclinD1. γ-Al2 O3 -5-FU increased the oxidative stress in cancer cells. Abstract: 5-Fluorouracil (5-FU) is being used in the treatment of several malignancies, but side effects are often reported and include: diarrhea, vomiting, nausea, poor appetite, watery eyes, and photophobia. We have developed and tested the cytotoxic activity of nanocrystalline powder of γ-alumina (γ-Al2 O3 ) containing 5-FU in two-dimensional and three-dimensional (3D) CRC cell culture. γ-Al2 O3 was prepared using a facile sol–gel method. The physicochemical properties of nanoparticles were investigated by Fourier Transform Infrared (FTIR) analysis, Field Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive X–ray Analysis (EDXA). Moreover, the particle size was monitored by Transmission Electron Microscopy (TEM). We used MTT and a scratch assay to assess the antiproliferative and anti-migratory of this agent. The effect of γ-Al2 O3 -5-FU on SOD, MDA, and total-thiols levels were evaluated. We assessed the expression of apoptotic markers in mRNA or proteins by RT-PCR and ELISA respectively. γ-Al2 O3 -5-FU inhibited cell growth in two-dimensional (2D) and three-dimensional (3D) cell culture and increased apoptosis as detected by DAPI stainning via modulation of caspases, BAx, BCl2 and cyclinD1. γ-Al2 O3 -5-FU also reduced the migratory activity of CRC cells relative to untreated controls. γ-Al2 O3 -5-FU increased the level of MDA, while reducing the level of SOD and total-thiols as well as inflamatory markers (e.g., TNF-s and IL-6). Our study demonstrated that γ-Al2 O3 -5-FU inhibited cell growth and migration, indicating its potential value in the treatment of colorectal cancer.